Feasibility study for proton dose calculation of esophageal squamous cell carcinoma based on stopping power ratio directly derived from dual energy CT - Li, Miaomiao; Cui, Yongbin; Lin, Xinjun; Yan, Yuanyuan; Liu, Qianyu; Nie, Mingming; Ye, Wenzhen Gong; Huang, Yong; Chen, Jinhu; Yin, Yong (Frontiers in Oncology, 2025)
PurposeTo investigate the feasibility of proton therapy planning using stopping power ratio (SPR) maps directly generated from spectral CT raw data, and to perform a comparative evaluation of dose calculation uncertainties between SPR maps derived from conventional CT Hounsfield Unit (HU) conversion and direct spectral CT SPR generation.Materials and methodsA retrospective analysis was conducted on 30 patients with mid-thoracic esophageal squamous cell carcinoma (ESCC) who underwent pre-treatment spectral CT imaging. Target volumes and organs at risk (OARs) were delineated on contrast-enhanced CT images and subsequently registered to both non-contrast CT and SPR maps. Three treatment plans were generated: Intensity-modulated radiotherapy (IMRT) plan based on conventional CT, Intensity-modulated proton therapy (IMPT) plan using HU-SPR conversion, IMPT plan utilizing direct SPR maps (IMPT-SPR) from spectral CT. Dose-volume parameters for target volumes and OARs (lungs, heart, spinal cord) were systematically analyzed. Comparative dosimetric analyses were performed among the three plans and between paired groups.ResultsAll plans met clinical radiotherapy requirements. For OARs (lungs, heart), IMPT plans demonstrated significantly lower dose-volume parameters compared to IMRT, except for maximum dose (Dmax). Between the two IMPT approaches, no statistically significant differences were observed in dose-volume parameters (p>0.05), except for the gradient index which was significantly higher in the HU-converted IMPT plan (p<0.05). No significant differences were detected in heart, lung and spinal cord dosimetric parameters between IMPT approaches.ConclusionIMPT demonstrated superior OAR sparing compared to IMRT. For mid thoracic ESCC patients under proton therapy, dose calculations based on CT-HU conversion was showed comparable dosimetric impact to DECT-derived SPR in terms of target coverage and OAR protection. These findings support the clinical feasibility of conventional CT-based proton therapy planning and dose calculation.